Author Correction: Influence of microstructure on superconductivity in K x Fe2−y Se2 and evidence for a new parent phase K2Fe7Se8 - Xiaxin Ding (Nature Portfolio, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.